Elections, Governance and Development in Nigeria - ORJI, Nkwachukwu (Socialscientia: Journal of Social Sciences and Humanities, 2021)
Political and development theories present free, fair and credible elections as sine qua non for good governance and development. However, while the literature focuses on the link between free, fair and credible elections, good governance, and development; not much attention have been devoted to the implications of flawed elections on governance and development. Lack of attention on the impact of flawed elections on governance and development particularly applies to countries like Nigeria with long history of flawed elections and extensive record of development and governance challenges. Assessments of elections in Nigeria, for example, are largely focused on bringing out the fundamental flaws of election management without analyzing the developmental implications of flawed elections. To complement the existing literature, this article looks at the ways in which elections have influenced governance and development in Nigeria. It contends that flawed elections reflect in shoddy governance which in turn has impeded development. At the end, the article suggests ways in which the electoral process can be modified to support good governance and development in Nigeria.